Effect of Osteoarthritis on Accuracy of Continuous Tracking Leg Movement. Issue 1 (February 2014) - Williamson, Elizabeth Mae; Marshall, Philip H.
The purpose of this study was to establish if osteoarthritis in older adults was associated with ability to accurately and continuously track leg movement in a model of therapy to improve age-related impairments of proprioception, kinesthesia, and coordination of muscles at the knee joint. 24 older adults without osteoarthritis and 24 older adults with osteoarthritis participated. Software generated a moving, on-screen sine wave and a vertically traveling disc. Participants attempted to keep the disc on the sine wave by bending and straightening the leg. Older adults without osteoarthritis performed better than older adults with osteoarthritis in one of two conditions. There was a relationship between osteoarthritis and reduced accuracy of leg movement. Further research will be required to specifically define this relationship and to establish if such interventions to improve accuracy of knee movement will positively affect functional capabilities of individuals with osteoarthritis.